Gender Equality in Politics from the Perspective of Civics Students: A Study of the Level of Awareness and Support for Women's Political Participation - Abdul Halim; Nuraini Fitriana; Rifka Silmia Salsha Bella; Novia Irmani Putri; Irawati Irawati (Penerbit Hellow Pustaka, 2026)
Gender equality in politics is one of the main indicators of an inclusive and just democracy. Although there have been various affirmative regulations in Indonesia such as a 30% quota for women in legislative candidacy, the reality of women's participation in politics still shows significant gaps. This phenomenon is a challenge in realizing equal political representation between men and women. This study aims to analyze how awareness and support for women's political participation are interpreted by students of the Pancasila and Citizenship Education (PPKn) Study Program as prospective educators and agents of social change. The method used is a descriptive quantitative approach by distributing closed questionnaires to 100 active students who have taken courses related to democracy, human rights, and gender. The results of the study show that in general students have a normative understanding of the importance of gender equality, but there is still ambivalence in providing concrete support for women's leadership in the political realm. Patriarchal cultural values, religious influences, and gender stereotypes are factors that influence the level of support. These findings indicate that although there is conceptual awareness, the internalization of gender equality values ​​in practice still needs to be strengthened. This study recommends the need for more explicit integration of gender perspectives in the curriculum and learning of PPKn in higher education.